The Multifaceted Impact of COVID‐19 on the Female Academic Emergency Physician: A National Conversation. Issue 1 (21st October 2020) - Das, Devjani; Lall, Michelle D.; Walker, Laura; Dobiesz, Valerie; Lema, Penelope; Agrawal, Pooja
Abstract: COVID‐19 has impacted all health care professionals in every aspect of life. Female academic emergency physicians have been uniquely affected and continue to face challenges related to clinical workloads, work–life integration, academic productivity, leadership and visibility within departments, and mental health. This white paper, prepared on behalf of the Academy for Women in Academic Emergency Medicine (AWAEM), describes the differential impact of COVID‐19 on female academic emergency physicians explored during a virtual panel discussion at the 2020 Society for Academic Emergency Medicine Annual Meeting. AWAEM convened a virtual panel of women to begin a discussion to share experiences and challenges and formulate consensus guidelines regarding best practices and mitigation strategies. The authors describe the unique ways in which female academic physicians have been affected, identify ongoing and intensified gender gaps, and delineate strategies to address the identified problems. Specific recommendations include individual, as well as, institutional and systems‐level approaches to combat the inequities.